Cerebral desaturations in preterm infants: a crossover trial on influence of oxygen saturation target range. Issue 5 (2nd March 2013) - Schmid, Manuel B; Hopfner, Reinhard J; Lenhof, Susanne; Hummler, Helmut D; Fuchs, Hans
Abstract : Objective: To test the hypothesis that a higher pulsoximetric arterial oxygen saturation (SpO2 ) target range is associated with reduced cerebral tissue oxygen desaturations from baseline during events of hypoxaemia or bradycardia. Design: Randomised crossover trial. Setting: Single tertiary care neonatal intensive care unit. Patients: Sixteen preterm infants with severe intermittent hypoxaemia or bradycardia. Interventions: SpO2 target was set to 80–92% and 85–96% for 4 h each in random sequence. On a subsequent day, the target sequence was reversed and the study was repeated. Main outcome measures: We simultaneously recorded cerebral tissue oxygen saturation (cerebral StO2 ), SpO2 and heart rate. Cerebral StO2 was measured by near infrared spectroscopy. The primary outcome was the cumulative cerebral StO2 desaturation score representing the area below a cerebral StO2 baseline value before onset of each hypoxaemic or bradycardic event. Results: During low SpO2 target range the median (IQR) cumulative cerebral StO2 desaturation score was higher (27384 (15825–37396) vs 18103 (6964–32946), p=0.011) and the mean (±SD) number of events was higher (29.1 (±15.3) vs 21.1 (±11.4), p=0.001). More time was spent with SpO2 below 80% (57.2 (±24.8) min vs 34.0 (±29.6) min, p=0.006). Total time of hyperoxaemia (defined as SpO2 ≥97% and ≥99%, respectively) and total time with cerebral StO2 <60% and <55% were similar. Conclusions: A lower SpO2 target range was associated with a greater cumulative cerebral StO2 desaturation score, caused by more frequent SpO2 desaturations. However, time at very low cerebral StO2 was not affected. Episodes of hyperoxaemia were not reduced.